Azerbaijan Economic Report, Spring 2014 : Public Investment Still Driving Growth - World Bank (World Bank, Washington, DC, 2017)
This regular economic report records the economic activities of Azerbaijan for the year 2013-2014. Economic growth continued to be powered by spending of previously accumulated oil-related proceeds, although the stabilization of oil production also helped. The non-oil sector grew by 10 percent in 2013, essentially aided by public investment. In addition, efforts aimed at stabilizing oil production bore fruit and resulted in an increase of 0.9 percent in oil output. The fiscal surplus narrowed to 1.8 percent of GDP in 2013 because of lower oil revenues and sustained expenditures, and the non-oil fiscal deficit continues to be high. The 2014 budget signals fiscal consolidation, essentially through lower public investments, a step in the right direction. With the announcement of 2014 as the Year of Industry, the authorities intend to prioritize adoption of the competition code, establishment of special economic zones and techno parks, winemaking, and other agricultural products. A modest increase in public expenditures on health and education in 2014 adds to the concerns that the government’s efforts at diversification might not be focused on strengthening its asset base.